Training Research Skills for High School Students in Vietnam: A Case Study - Hiep-Hung Pham; Linh-Chi Nguyen (Vietnam Journal of Education)
This article presents a case study in Vietnam where a course on research skills was taught to outstanding high school students who are preparing to study abroad. The course is structured with training sessions that focus on key ideas in scientific research, reading and writing skills, and research projects in which students help complete a review article. The article investigates the possibilities of integrating such a course into the Vietnamese high school system, as well as the obstacles to implementation. The course embraces promise for growth as Vietnamese parents and students become more aware of the need for research skills despite facing obstacles such as time limitations and passive learning preferences. Vietnam and SouthEast Asia is a major market for student mobility, highlighting a strong demand for international higher education. More emphasis should be placed on courses that specifically equip secondary students with research abilities and overall college readiness skills. The noted difficulties can be overcome to deliver high-quality research skills courses for high school learners.